Lunatics [compact disc, unabridged] - Barry, Dave (Penguin Audio, 2012)
Philip Horkman is a happy man - the owner of a pet store called the Wine Shop, and on Sundays a referee for kids' soccer. Jeffrey Peckerman is the sole sane person in a world filled with jerks and morons, and he's having a really bad day. The two of them are about to collide in a swiftly escalating series of events that will send them running for their lives, pursued by the police, soldiers, terrorists, subversives, bears, and a man dressed as Chuck E. Cheese.